Haskell data analysis cookbook : explore intuitive data analysis techniques and powerful machine learning methods using over 130 practical recipes /: explore intuitive data analysis techniques and powerful machine learning methods using over 130 practical recipes. (2014) - Shukla, Nishant, 1992-
No abstract available